The Effect of Temperature on the Development of Trilocha varians (Lepidoptera: Bombycidae) and Control of the Ficus Plant Pest - Norasmah Basari,; Nurul Salsabila Mustafa,; Nur Elya Nabila Yusrihan,; Chin Wei Yean,; Zainal Ibrahim, (Tropical Life Sciences Research, 2019)
Ficus plants are commonly planted as ornamentals along roadsides in Malaysia. In 2010, Ficus plants in Kuala Terengganu were found to be attacked by a moth, identified as Trilocha varians. The larvae of this moth fed on Ficus leaves causing up to 100% defoliation. This study was conducted to determine the life cycle of T. varians under two different environmental temperatures and to control this pest using two different insecticides. Our findings showed that there were significant differences in the time taken for eggs to hatch and larval and pupation period between low and high environmental temperatures. Results also showed that fipronil had lower LT50 and LT95 than malathion. This study provides new information on the life history of T. varians under two different conditions and the efficiency in controlling T.varians larvae using insecticides. The results of this study are important for future management in controlling T. varians population especially in Kuala Terengganu, Malaysia. Pokok Ficus biasa ditanam sebagai tanaman hiasan di sepanjang jalan raya di Malaysia. Pada tahun 2010, pokok Ficus di Kuala Terengganu didapati telah diserang oleh kupu-kupu yang dikenali sebagai Trilocha varians. Larva kupu-kupu pemakan daun ini boleh menyebabkan pokok Ficus mengalami kehilangan daun sehingga 100%. Kajian ini dijalankan untuk menentukan kitar hidup T. varians di bawah dua suhu persekitaran yang berbeza dan untuk mengawal serangga perosak ini menggunakan dua jenis insektisid. Keputusan menunjukkan terdapat perbezaan yang signifikan bagi masa yang diambil untuk telur menetas dan jangka masa bagi larva dan pupa di antara suhu persekitaran rendah dan tinggi. Keputusan juga menunjukkan fipronil mempunyai LT50 dan LT95 yang rendah berbanding malathion. Kajian ini memberi maklumat baharu berkaitan kitar hidup T. varians di bawah dua keadaan berbeza serta kecekapan kawalan larva T. varians menggunakan insektisid. Keputusan kajian ini penting untuk pengurusan kawalan populasi T. varians pada masa hadapan terutamanya di Kuala Terengganu, Malaysia.